(untitled) (Philological Studies, 2019)
The problem of lexical equivalents in the process of interlanguage translation has been considered in the article. Taking into consideration the fact that a word is the basis of any decoding as well as the interlanguage one, the authors analyse the phenomenon of word untranslatability caused by the difference of language and conceptional world images. Hence, a word has been considered as a concept carrier. Relying on the opinion that word untranslatability is the objective reality, the contrastive analysis of the so-called lexical interlanguage equivalents has been conducted in the article. ’Nevsky Prospekt’ by N. Gogol and its translation into English has been taken as the material for the analysis. While comparing a word of source language with a word of target language three zones have been marked: the zone of meaning of a source language word; the zone where meanings of words coincide; and the zone of meaning of a target language word.